Devolution and its discontents - Hepworth, J (History & Policy, 2022)
The Conservative government insists that modifying the Northern Ireland Protocol will entice the Democratic Unionist Party back into Stormont and restore the devolved Assembly. But the current crisis highlights deeper unionist disillusionment with power-sharing.